Entrepreneurial Resilience in Micro and Small Enterprises: A Case Study in Makassar - Isma Azis Riu; Welimas Kristina Parinsi (Maksimal Jurnal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2024)
This research investigates resilience strategies among micro and small entrepreneurs facing economic uncertainty in Makassar. Through narrative inquiry, the study captures lived experiences of business owners navigating financial instability and market disruptions. Findings indicate that resilience is shaped by social capital, religious values, and adaptive marketing practices. Entrepreneurs demonstrate flexibility in pricing, product innovation, and customer engagement. The study contributes to entrepreneurship theory by contextualizing resilience within socio-cultural dynamics and recommends policy interventions focusing on community-based support systems.